Overcoming the challenges to develop the future of E-government in Iraq: a systematic literature review - Al-Yawer, Harith; Ahmad, Rahayu (Science Publishing Corporation Inc, 2018)
Despite the early start that Iraq had in the e-government project and its launch in 2004, the pace of development is rather slow. This study aims to identify the main themes of the technical challenges hindering the development of e-government in Iraq. Systematic literature review was employed in this study to collect and analyse papers published on e-government in Iraq to reveal the main themes of the technical challenges in e-government projects. The result obtained from the systematic literature review revealed six themes of technical challenges. These identified challenges are important to be addressed to accelerate the progress of e-government in Iraq.